Proliferation Security Initiative (PSI): Revisiting the Indonesian Perspective - Muhamad Jaki Nurhasya (AEGIS : Journal of International Relations, 2017)
The Proliferation Security Initiative (PSI) is regarded as one of the most aggressive and impactful worldwide efforts conducted to contain the spread of WMD materials and delivery system.Despite heavy pressure from the United States and its palpable position on the world’s maritime counter-terrorism and WMD effort, Indonesia has always maintained a position of non-participation towards the initiative. This article identified principles of sovereignty and foreign policy trajectory as one of the main hindering factor behind Indonesia’s refusal and proposes a re-evaluation towards both the initiative and Indonesia’s national position.